(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
After considering these factors, the topic Impact of Mergers and Acquisition on FinancialPerformance of Indian Commercial Banks was selected. Mergers and acquisitions are essential to acompany’s development and growth in today’s competitive global market. The purpose of banking is toaccess money via various ways, such as a cheque or electronic transfer, and to return borrowed orinvested funds when required (such as a draught). The Grand Bank of India and the Bank of Hindustanwere the first Indian banks to open for business in 1786. Unfortunately, the two banks that were citedbefore no longer operate. Kolkata is home to one of India’s first banks, the Bank of Calcutta, it has beenin existence since 1806 and was once called the State Bank of India. The Bank of Bengal (BOM), the Bankof Bombay (BOM), and the Bank of Madras (BOM) were all founded by the East India Company between1809 and 1840, 1843, respectively (BOM). Increased cross-border MA activity is having a noticeableimpact on the size of banking sector transactions. Notwithstanding the current economic situation, thequest of a strategic advantage is still motivating certain acquisitions. Dealmakers for SPACs are underpressure to emphasize revenue growth above cost savings in order to justify high values for theiracquired assets in an environment where SPACs are expected to compete with corporate and privateequity bidders for the most acceptable assets.